Assisted partner notification services are cost-effective for decreasing HIV burden in western Kenya. (14th January 2018) - Sharma, Monisha; Smith, Jennifer A.; Farquhar, Carey; Ying, Roger; Cherutich, Peter; Golden, Matthew; Wamuti, Beatrice; Bukusi, David; Spiegel, Hans; Barnabas, Ruanne V.
Abstract : Background: Assisted partner services (aPS) or provider notification for sexual partners of persons diagnosed HIV positive can increase HIV testing and linkage in Sub-Saharan Africa and is a high yield strategy to identify HIV-positive persons. However, its cost-effectiveness is not well evaluated. Methods: Using effectiveness and cost data from an aPS trial in Kenya, we parameterized an individual-based, dynamic HIV transmission model. We estimated costs for both a program scenario and a task-shifting scenario using community health workers to conduct the intervention. We simulated 200 cohorts of 500 000 individuals and projected the health and economic effects of scaling up aPS in a region of western Kenya (formerly Nyanza Province). Findings: Over a 10-year time horizon with universal antiretroviral therapy (ART) initiation, implementing aPS in western Kenya was projected to reach 12.5% of the population and reduce incident HIV infections by 3.7%. In sexual partners receiving aPS, HIV-related deaths were reduced by 13.7%. The incremental cost-effectiveness ratio of aPS was 1094 (US dollars) (90% model variability 823–1619) and 833 (90% model variability 628–1224) per disability-adjusted life year averted under the program and task-shifting scenario, respectively. The incremental cost-effectiveness ratios for both scenarios fall below Kenya's gross domestic product per capita (1358) and are therefore considered very cost-effective. Results were robust to varying healthcare costs, linkage to care rates, partner concurrency rates, and ART eligibility thresholds (⩽350 cells/μl, ⩽500 cells/μl, and universal ART). Interpretation: APS is cost-effective for reducing HIV-related morbidity and mortality in western Kenya and similar settings. Task shifting can increase program affordability. Abstract : Supplemental Digital Content is available in the text